Mental accounting in tax evasion decisions: An experiment on underreporting and overdeducting - Martin Fochmann; Nadja Wolf (Arbeitskreis Quantitative Steuerlehre (arqus), 2015)
Although there is already a variety of papers analyzing tax evasion decisions, only little focus is put on tax evasion of gains and losses. As taxpayers can evade taxes by either underreporting their income or by overdeducting expenses, we study whether there is a significant difference if subject are confronted with a gain or a loss scenario. We find that individuals evade more in the first than in the latter case. As a consequence, subjects are more willing to evade taxes by underreporting income than by overdeducting expenses. We show that this finding can be explained by mental accounting and an asymmetric evaluation of tax payments and tax refunds. Our result is robust to treatment variation. However, if individuals have to complete only one tax declaration (but still decide on gains and losses) and we therefore expect subjects to use only one mental account, the effect vanishes. This provides strong evidence that mental accounting plays an important role in tax evasion decisions. Further results are presented and discussed.
Keywords: C91; D14; H24; 330; tax evasion; tax compliance; prospect theory; mental accounting; behavioral taxation; experimental economics